Spectroscopic and geometrical evolution of the ejecta of the classical nova ASASSN-18fv. Issue 2 (5th May 2020) - Pavana, M; Raj, A; Bohlsen, T; Anupama, G C; Gupta, Ranjan; Selvakumar, G
ABSTRACT: The optical spectroscopic observations of ASASSN-18fv observed from 2018 March 24 to 2019 January 26 are presented. The optical spectra are obtained from Mirranook, Vainu Bappu, and South African Astronomical observatories. The spectra are dominated by the hydrogen Balmer, Fe ii, and O i lines with P-Cygni profiles in the early phase, typical of an Fe ii class nova. The spectra show He i lines along with H i and O i emission lines in the decline phase placing the nova in the hybrid class of novae. The spectra show rapid development in high-ionization lines in this phase. Analysis of the light curve indicates t 2 and t 3 values of about 50 and 70 d, respectively, placing the nova in the category of moderately fast nova. The ejectum geometry, inclination, and position angle are estimated using morpho-kinematic analysis. The geometry of the ejecta is found to be an asymmetric bipolar structure with an inclination angle of about 53 ○ . The ejected mass using photoionization analysis is found to be 6.07 × 10 −4 M⊙ .